Tool for optimum planting window selection NG-Akilimo-SAA: manual for executing and managing the decision support tool for variety selection and planting window recommendation - Benito, E.G.; Peter, H.; Tofa, A.I.; Tijjani, K.; Kamara, A.; Kreye, C. (International Institute of Tropical Agriculture, 2023)
Seasonal variability is a major constraint for many farmers cultivating maize under rainfed conditions in Northern Nigeria. Climate change is resulting in more erratic seasonal weather patterns and limiting the ability of farmers to rely on previous knowledge of the farming system where they operate. The Variety and Planting Window Recommendation Decision Support Tool (DST) for the EiA SAA - Nigeria use case aims to provide farmers with spatially explicit recommendations on optimal variety and planting window combinations. The recommendations are based on DSSAT v47 using a spatialization framework and consuming data from iSDA soil, CHIRPSv2 and ECMWF AgERA5. Additionally, calibrated cultivar coefficients are used to reproduce the local behavior of maize varieties in the target area. The tool is expected to be updated every cropping season (year), to account for the previous year’s conditions on the recommendations.